Efficacy of metoprolol and diltiazem in patients with mild and moderate mitral stenosis in sinüs rhythm - ALAN Feridun KOSAR Ismet HISAR Telat KELES Siber GOKSELYuksek Ihtisas Hastanesi Kardiyoloji Klinigi ANKARA, Sait; TURKEY. (Annals of Medical Research, 2021)
None